1985
DOI: 10.1073/pnas.82.13.4531
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical correlates of the distribution of the pathological changes in the neocortex in Alzheimer disease.

Abstract: The numbers and distribution of the neurofibrillary tangles and neuritic plaques have been determined in several areas of the neocortex in brains affected by various degrees of severity of Alzheimer disease. The homotypical cortex of the "association" areas of the temporal, parietal, and frontal lobes are severely involved, whereas the motor, somatic sensory, and primary visual areas are virtually unaffected. The neurofibrillary tangles are mainly in the supra-and infragranular layers, particularly in layers I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
418
3
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 845 publications
(470 citation statements)
references
References 27 publications
39
418
3
2
Order By: Relevance
“…Neuropathologic studies in AD (Pearson et al 1985) indicate maximal involvement of association areas and minimal involvement of primary sensory areas. However, an ophthalmologic study found evidence for a widespread visual dysfunction in AD (Cronin-Golomb et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathologic studies in AD (Pearson et al 1985) indicate maximal involvement of association areas and minimal involvement of primary sensory areas. However, an ophthalmologic study found evidence for a widespread visual dysfunction in AD (Cronin-Golomb et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The locally synthesized ATF4 is retrogradely transported in a dynein-dependent manner to the neuronal cell bodies, ATF4 levels and ATF4-dependent transcription in the neuronal soma increase, and ATF4-dependent expression of CCAATenhancer-binding protein homologous protein (CHOP) is upregulated leading to cell death. Pathological changes in AD spread through the brain in a nonrandom manner that indicates propagation along connecting fiber tracts [57]. The molecular mechanisms driving the spread of pathology remain largely unknown.…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…Thus, loss of synaptic contacts in associative cortices and limbic structures would interrupt long connecting pathways in AD (Hyman et al, 1984;Pearson et al, 1985). The relative preservation of automatic processes in AD patients would mean that these processes are subserved by circumscribed cortical areas that are less affected by disconnection in the early stages of the disease.…”
Section: Neural Substrate Of Controlled Processesmentioning
confidence: 99%